Advances in Antifungal Development: Discovery of New Drugs and Drug Repurposing - Jong H. Kim; Luisa W. Cheng; Kirkwood M. Land (MDPI AG, 2022)
This Special Issue of Pharmaceuticals describes recent advances accomplished in the field of antifungal development, especially the discovery of new drugs and drug repurposing [...]